Just you, and I, waiting - The poetry of Psalm 25 - Doyle, Brian (Old Testament Essays, 2001)
The present article endeavours to determine some of the structuring and non structuring poetic features of Psalm 25. At the same time, an effort is made to establish priority among the psalm's poetic features, partivularly between the acrostic and the concentric aspects thereof. The article concludes that the history of exegesis of this psalm has been distracted by its acrostic form and has thus tended to ignore its concentric structure. The latter serves as the psalm's primary meaning bearing feature, focusing the reader's attention on the central verse 11 in which the psalmist pleads for forgiveness in the context of anintimate direct address to YHWH.
free
Keywords: Christianity; Psalm 25